TIBBIY PARAZITOLOGIYANING BIOLOGIYA VA TIBBIYOTDAGI O‘RNI VA AHAMIYATI. (Multidisciplinary Journal of Science and Technology, 2025)
This article highlights the role of parasitology in human biology and chemistry, itsimpact on health, and precautionary measures. Parasitology is an important scientificfield that studies parasites living in the human body, their development, and theirbiological and medical properties. Worldwide, there are over 300,000 known parasitespecies, with each human on average hosting three types of parasites. In biology,parasitology helps to understand the mechanisms of parasite effects on human cells andorgans. In chemistry, it studies metabolic processes, toxins, and biologically activesubstances related to parasites, which is crucial for developing new medications.Furthermore, parasitology plays a vital role in maintaining human health, preventingand treating diseases, and emphasizes the importance of personal hygiene and safetymeasures.